Implementation of Marpol 73/78 Annex I to prevent oil spills at Tanjung Perak Port, Surabaya - Alam, Muhamad Helga Fairuuz; Bimantoro, Rafly Ramadhan (Journal of Marine Resources and Coastal Management, 2023)
The increase in shipping activities is directly proportional to the threat of oil spills in the ocean, both from operational activities and ship accidents. Port of Tanjung Perak Surabaya has heavy traffic and continues to increase every year. This condition can pose a threat of increasing the risk of oil spills. Appropriate actions are needed to minimize the percentage of oil spill threats, one of which is by enforcing MARPOL 73/78 regulations which are intended for tankers. Specifically, MARPOL 73/78 Annex 1 is a regulation regarding marine pollution caused by oil or its derivatives from ship operational activities or accidental discharge of oil. This problem is the basis for the need to carry out research regarding the study of the implementation of MARPOL 73/78 Annex I to prevent oil spills at the Tanjung Perak Port, Surabaya, especially at the Nilam Terminal. Through distributing questionnaires, it was discovered that the prevention of oil spills at the Nilam Terminal-Tanjung Perak Port, Surabaya, carried out by 5 tankers, had an average assessment score of 18.4 or 92%, which means that the majority of oil tankers were very good at implementing international standards. MARPOL regulation 73/78 Annex I at Tanjung Perak Port, Surabaya.